Health complexity assessment in primary care: A validity and feasibility study of the INTERMED tool. - Camila Almeida de Oliveira; Bernardete Weber; Jair Lício Ferreira Dos Santos; Miriane Lucindo Zucoloto; Lisa Laredo de Camargo; Ana Carolina Guidorizzi Zanetti; Magdalena Rzewuska; João Mazzoncini de Azevedo-Marques (PLoS ONE)
Background Health complexity includes biological, psychological, social, and health systems. Having complex health needs is associated with poorer clinical outcomes and higher healthcare costs. Care management for people with health complexity is increasingly recommended in primary health care (PHC). The INTERMED complexity assessment grid showed adequate psychometric properties in specialized settings. This study aimed to evaluate INTERMED's validity and feasibility to assess health complexity in an adult PHC population. Method The biopsychosocial health care needs of 230 consecutive adult patients from three Brazilian PHC services were assessed using the INTERMED interview. Participants with a total score >20 were classified as "complex". Quality of life was measured using the World Health Organization Quality of Life BREF (WHOQOL-BREF); symptoms of anxiety and depression using the Hospital Anxiety and Depression Scale (HADS); social support using the Medical Outcomes Study-Social Support Survey (MOS-SSS); comorbidity levels using the Charlson Comorbidity Index (CCI). We developed two questionnaires to evaluate health services use, and patient perceived feasibility of INTERMED. Results 42 participants (18.3%) were classified as "complex". A moderate correlation was found between the total INTERMED score and the total scores of WHOQOL-BREF (rho = - 0.59) and HADS (rho = 0.56), and between the social domains of INTERMED and MOS-SSS (rho = -0.44). After adjustment, the use of PHC (β = 2.12, t = 2.10, p < 0.05), any other health care services (β = 3.05, t = 3.97, p < 0.01), and any medication (β = 3.64, t = 4.16, p < 0.01) were associated with higher INTERMED scores. The INTERMED internal consistency was good (ω = 0.83), and the median application time was 7 min. Patients reported satisfaction with the questions, answers, and application time. Conclusion INTERMED displayed good psychometric values in a PHC population and proved promising for practical use in PHC.